Malignant Mixed Germ Cell Tumors of the Ovary: A Series of Rare Cases - Goyal, Lajya Devi (J Reprod Infertil, 2019)
BACKGROUND: Malignant mixed germ cell tumors of ovary are rare aggressive cancers affecting young adolescent girls. The commonest combination reported in literature is dysgerminoma and endodermal sinus tumors but in our study the most common combination was immature teratoma and endodermal sinus tumor which is exteremely rare. Preservation of future fertility is a concern. Fertility sparing surgery followed by combination chemotherapy is the current treatment of choice but treatment must be individualized depending upon the nature of the tumor. METHODS: A retrospective study on five patients with these tumors was conducted on patients at Guru Gobind Singh Medical College and Hospital (Punjab, India) between September 2009 to January 2018. RESULTS: Median age of patients was 15.6 years. Histopathological combination was immature teratoma and endodermal sinus tumor (n=3), endodermal sinus tumor and embryonal carcinoma (n=1), and mature and immature teratoma (n=1). Tumor markers AFP, beta HCG and LDH were raised in all except the patient with mature and immature teratoma. All patients underwent surgery followed by combination chemotherapy. Three patients developed metastasis within six months of treatment and died. In the remaining two, no reccurrence was reported till date. CONCLUSION: Malignant mixed germ cell tumors of ovary are extremely rare tumors and have poor prognosis. Fertility preservation is a concern as these patients are usually young adolescent girls but fertility sparing treatment must be individualized on the basis of tumor type, surgical staging, and availability of combination chemotherapy. Considering high recurrence rate and mortality, total hysterectomy with bilateral salpingo-oophorectomy with complete surgical staging followed by combination chemotherapy should be perfomed at advanced stage and aggressive tumor biology. Preservation of fertility must be held secondary.